443 COVID19 disease severity influences the expression of markers of durability in memory B cells. (April 2022) - Reyes, Raphael; Clarke, Kathleen; Cantwell, Angelene M.; Catano, Gabriel; Tragus, Robin E.; Patterson, Thomas F.; Bol, Sebastiaan; Bunnik, Evelien M
Abstract : OBJECTIVES/GOALS: Studies have shown that SARS-CoV-2 specific memory B cells can be maintained at least a year after exposure. However, reports show an altered B cell response during infection in severe COVID-19 cases. This study aims to describe the B cell response during COVID-19 convalescence with a focus on signatures that contribute to durable and robust immunity. METHODS/STUDY POPULATION: Our study cohort consisted of individuals who had recovered from non-severe (hospitalized) or severe (hospitalized and requiring invasive mechanical ventilation) COVID-19. In our comparative analysis, samples from both groups were carefully matched to fall within 4-5 weeks post-symptom onset. We also performed a longitudinal analysis of non-severe patients with sampling ending 5 months post-symptom onset. Using high parameter flow cytometry, we characterized the phenotype of memory B cells using 19 distinct cell markers and fluorescently labeled probes to identify B cells reactive with SARS-CoV-2 spike and receptor-binding domain protein. Additionally, serum collected from individuals was used to quantify antibody titers. RESULTS/ANTICIPATED RESULTS: The frequency of spike-specific B cells and serum antibody titers were similar between severe and non-severe groups. However, we observed that individuals recovered from severe COVID-19 have a significantly reduced frequency of spike specific IgG+ memory B cells expressing Tbet and FcRL5 (markers associated with long lived immunity). In the non-severe patients, we observed IgG+Tbet+ B cells targeting the spike protein peak at 2-3 weeks post-symptom onset, decrease by almost fifty percent 4-5 weeks post-symptom onset, and return to baseline 5 months post-symptom onset. Our study also validated previous findings of a short-lived primary response of IgM+ B cells targeting the spike protein. DISCUSSION/SIGNIFICANCE: Our findings highlight potential implications for long-term immunity against re-infection or severity of the resulting disease in patients with severe COVID-19. Further investigation will be necessary to determine whether the maintenance of immunological protection is hindered in patients who overcame severe COVID-19.